Controlling constructions risks in energy projects - Al Ali, Humaid Salim Ali Hassan (2017)
A risk is a natural phenomenon present in all construction projects. The challenge lies in dealing with such risks. Construction in energy projects is more challenging and demanding, risks present are not only more severe in terms of consequences, but they require tremendous amount of effort and analysis to deal with. The paper provides insight to the energy construction industry, the risks that are associated with it, and how such risks are being identified, classified, mitigated and sometimes avoided. Energy projects can be found in oil and gas, renewable and nuclear energy projects. Examples from the UAE, Europe and China were taken into the study and further emphasis on the risk aspects and nature have been identified and explained. The paper offers a variety of risks associated with the energy industry with a special emphasis on the construction phase. The course of paper involves the identification, management, control and mitigations of risks. Methods used and applied on the management of risks are also discussed, which offers a transient interchange and exchange of experiences between the different sub sectors of the energy construction industry. !